The political economy of Stalinism : evidence from the Soviet secret archives - Gregory, Paul R. (Cambridge University Press, 2004)
Using formerly secret Soviet state and Communist Party archives to describe the Soviet administrative command system, this study concludes that the system failed not because of Stalin and later leaders, but because of the economic system. It pinpoints the reasons for failure such as poor planning, unreliable supplies, preferential treatment of indigenous enterprises as well as the basic principal-agent conflict between planners and producers, which created a sixty-year reform stalemate. Although the command system was the most significant human experiment of the twentieth century, its basic contradictions and inherent flaws would re-surface if it were to be repeated.--Publisher description.